Academic Precariat: Practicing Social Sciences in Iran - ʿArabistānī, Mihrdād ca. 20./21. Jh. (The Muslim world, 2025)
Academics increasingly experience precarity as job insecurity, stressful working conditions, uncertainty, stuckedness, and constraints on choosing their career paths. The sources of academic precarity are diverse, ranging from neoliberal economic strategies to gendered issues, intellectual leadership patterns, and political influences. In a country like Iran, where politics permeate all aspects of social and private life, research and practice in the social sciences invariably carry political implications. Research topics such as ethnicity, religion, social problems, and sexuality, which may critically address official political discourse, are considered sensitive and require a cautious approach. This situation affects various aspects of academic work, including selecting research subjects, writing styles, publication processes, faculty recruitment, job security, and the relationship between ethnographers/researchers and their interlocutors. The situation becomes even more complicated when foreign researchers are involved due to a chronic suspicion of foreigners. This type of academic precarity is underrepresented in scholarship because the precarious conditions faced by affected academics often prevent them from presenting their experiences. While viewing social science practice in Iran as a dichotomy between state prohibition and academic resistance is tempting, this perspective is overly simplistic. The dominant political discourse tolerates the transgression of the "unwritten laws of prohibition" to the extent that such actions do not overtly challenge the nodal points of the dominant political ideology. In other words, social scientists operate within a zone of permissiveness that allows some violations of prohibition laws. However, the right of investigation is reserved for the officials. Therefore, the situation is always shaky and paradoxically results in anxiety and precarity for academics.